Implementasi Metode Active Learning dalam Meningkatkan Motivasi dan Kualitas Pembelajaran Pendidikan Agama Islam (PAI) - Zahro, Nur Fatimatuz (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the implementation of the Active Learning method in improving motivation and the quality of Islamic Religious Education (PAI) learning at SMP NURUL HUDA. The background of this research is based on the low level of students' learning motivation and participation, which is influenced by the dominance of conventional teaching methods that lack student engagement. This study employed a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews with PAI teachers and eighth-grade students, and documentation of learning tools. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing/verification. Data validity was ensured through source triangulation, technique triangulation, member check, prolonged engagement, and audit trail. The results indicate that the Active Learning method significantly improves student engagement and learning motivation in PAI learning. Students become more active in discussions, presentations, and group work, creating a more interactive and participatory learning atmosphere. Furthermore, the Active Learning method provides more meaningful learning experiences, strengthening students' cognitive, affective, and spiritual aspects, including self-confidence, courage to express opinions, and internalization of Islamic values. However, implementation faces challenges such as time constraints and varying student characteristics. Therefore, teacher readiness and institutional support are essential for the successful implementation of the Active Learning method in PAI learning at the junior high school level